Malaria Parasites Hijack Host Receptors From Exosomes to Capture Lipoproteins - Iso-o, Naoyuki; Komatsuya, Keisuke; Tokumasu, Fuyuki; Isoo, Noriko; Ishigaki, Tomohiro; Yasui, Hiroshi; Yotsuyanagi, Hiroshi; Hara, Masumi; Kita, Kiyoshi (Frontiers in Cell and Developmental Biology, 2021)
Malaria parasites cannot multiply in host erythrocytes without cholesterol because they lack complete sterol biosynthesis systems. This suggests parasitized red blood cells (pRBCs) need to capture host sterols, but its mechanism remains unknown. Here we identified a novel high-density lipoprotein (HDL)-delivery pathway operating in blood-stage Plasmodium. In parasitized mouse plasma, exosomes positive for scavenger receptor CD36 and platelet-specific CD41 increased. These CDs were detected in pRBCs and internal parasites. A low molecular antagonist for scavenger receptors, BLT-1, blocked HDL uptake to pRBCs and suppressed Plasmodium growth in vitro. Furthermore, platelet-derived exosomes were internalized in pRBCs. Thus, we presume CD36 is delivered to malaria parasites from platelets by exosomes, which enables parasites to steal HDL for cholesterol supply. Cholesterol needs to cross three membranes (RBC, parasitophorous vacuole and parasite’s plasma membranes) to reach parasite, but our findings can explain the first step of sterol uptake by intracellular parasites.